An additional glucose dehydrogenase from Sulfolobus solfataricus: fine-tuning of sugar degradation?. (19th January 2011) - Haferkamp, Patrick; Kutschki, Simone; Treichel, Jenny; Hemeda, Hatim; Sewczyk, Karsten; Hoffmann, Daniel; Zaparty, Melanie; Siebers, Bettina
Abstract : Within the SulfoSYS ( Sulfolobus Systems Biology) project, the effect of temperature on a metabolic network is investigated at the systems level. Sulfolobus solfataricus utilizes an unusual branched ED (Entner–Doudoroff) pathway for sugar degradation that is promiscuous for glucose and galactose. In the course of metabolic pathway reconstruction, a glucose dehydrogenase isoenzyme (GDH-2, SSO3204) was identified. GDH-2 exhibits high similarity to the previously characterized GDH-1 (SSO3003, 61% amino acid identity), but possesses different enzymatic properties, particularly regarding substrate specificity and catalytic efficiency. In contrast with GDH-1, which exhibits broad substrate specificity for C5 and C6 sugars, GDH-2 is absolutely specific for glucose. The comparison of kinetic parameters suggests that GDH-2 might represent the major player in glucose catabolism via the branched ED pathway, whereas GDH-1 might have a dominant role in galactose degradation via the same pathway as well as in different sugar-degradation pathways.